1996
DOI: 10.1093/qjmed/89.11.839
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of brittle diabetes in Britain

Abstract: We investigated the prevalence and characteristics of 'brittle diabetes', defined as insulin-dependent diabetes mellitus associated with glycaemic instability of any type, leading to life disruption with recurrent and/or prolonged hospitalizations. A questionnaire was sent to all physicians and paediatricians running diabetic clinics in the UK, from lists held at the British Diabetic Association. A total of 414 brittle patients were reported (72% questionnaire return). Most were young (mean age +/- SD was 26 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
3
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 14 publications
2
47
3
1
Order By: Relevance
“…This is in contrast to studies in younger groups where recurrent DKA is usually the commonest (about 60%) form of instability 8 . Also, some studies in younger patients have shown a greater female excess than ours 5,12 , though this is not always a clear ®nding 7 Ðthus our ®gure of 71% female is not unlike the ®gure of 66% female in the large survey (n=414) by Gill et al 7 . The female excess in elderly brittle patients should not be interpreted too far, since there is a female excess in the elderly population in general.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…This is in contrast to studies in younger groups where recurrent DKA is usually the commonest (about 60%) form of instability 8 . Also, some studies in younger patients have shown a greater female excess than ours 5,12 , though this is not always a clear ®nding 7 Ðthus our ®gure of 71% female is not unlike the ®gure of 66% female in the large survey (n=414) by Gill et al 7 . The female excess in elderly brittle patients should not be interpreted too far, since there is a female excess in the elderly population in general.…”
Section: Discussioncontrasting
confidence: 47%
“…Recurrent and long hospital admissions are the rule 1,5,6 . Most patients with brittle diabetes are in the second or third decade of life 7,8 , and they are typically admitted with ketoacidosis (DKA) rather than hypoglycaemia or mixed patterns of instability 7± 9 . Grif®ths and colleagues have reported 6 older patients with brittle type 1 diabetes 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In a study aimed at verifying the trend of parasuicides from drug self-poisoning in 1987–1988 and 1992–1993, Bialas et al[4] confirmed the prevalence of such behaviours among females and a female/male ratio of 1.13:1.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with brittle diabetes are in the second or third decade of life and they are typically admitted with diabetic ketoacidosis rather than hypoglycemia or mixed patterns of instability. A "second peak" of prevalence at the age of 60-70 years has been recorded though much smaller than the main peak at 15-30 years (Gill et al, 1996). Causes for this "second round" of "brittleness" include medical disease (14%) , hypoglycemic unawareness (6%), and memory or behavioral problems (8%).…”
Section: Aetiology and Pathophysiologic Substrate: From The Suspicionmentioning
confidence: 99%
“…Emergency admissions due to poor diabetic control are much more common and prolonged than in "stable" patients, and it is not unusual for patients with brittle diabetes to spend several months each year in hospital. Pragmatic definitions of lifestyle disruption and "brittleness" include frequency and duration of hospitalization, more frequent psychosocial disruptions, pregnancy complications (Kent et al, 1994;Gill et al, 1996) and higher risk of death due to diabetic ketoacidosis, hypoglycemia, and renal failure . Epidemiological studies in patients with brittle diabetes have established higher prevalence rates of psychiatric disorders, in particular mood and anxiety disorders.…”
Section: Quality Of Life: Struggling Towards Its Achievementmentioning
confidence: 99%